Transformation of cultural values through classical literature in education - Burhanudin, Muhamad; Neina, Qurrota Ayu; Widianto, Eko (Universitas Mulawarman, 2025)
This research aims to investigate and identify research trends related to classical literature to preserve Islamic cultural heritage through education, especially in the context of religious education. The primary focus of this research is to examine the contribution of classical literature in the learning process and teaching of Islamic cultural and spiritual values. This study uses a bibliometric approach by analyzing 441 scientific documents from the Scopus database from 2004 to 2024. The data studied includes titles, keywords, and abstracts, with the help of VOSviewer software for visual mapping of keywords and research topic networks. The study has three main findings. First, the productivity of scholarly publications related to classical literature is still low, suggesting that this topic has not been extensively explored academically and has excellent opportunities for future development. Second, the keyword analysis uncovers several essential terms that can be the basis for developing new topics, particularly in the context of preserving Islamic culture through education. Third, there is great potential in making classical literature a vehicle for forming character and cultural values in the religious education system. Thus, studying classical literature as part of the Islamic cultural heritage requires a more systematic and interdisciplinary approach.